The Effect of Service Quality, Collection System, and Tax Sanctions on PBB-P2 Taxpayer Compliance in Brebes Regency - Muhammad Naufal Ashifuddin; Agung Yulianto (Global Writing Academica Researching and Publishing, 2026)
This study looked at how Service quality, the tax collection mechanism, and tax penalties all had an impact on taxpayers' compliance with the Rural and Urban Land and Building Tax (PBB-P2) in Brebes Regency. In order to get primary data, taxpayers were given questionnaires to complete. a survey method combined with a quantitative methodology. The information was assessed Multiple linear regression. The findings demonstrated that taxpayers were positively and significantly impacted by service quality compliance, indicating that better responsiveness, reliability, and assurance improved compliance behavior. Additionally, the tax collection system had a favorable and noteworthy effect, indicating that taxpayers were encouraged to fulfill their obligations by clear procedures, transparency, and ease of payment. Additionally, tax penalties proved to be the most important element influencing compliance and had a favorable and considerable impact. These results showed that raising the standard of public services, streamlining the tax collecting process, and imposing just and uniform penalties all improved taxpayer compliance. Local governments can use the study's practical findings to create policies that maximize local tax income and boost compliance.